Determinants of tourist attitudes toward local food and intentions to visit a destination: A case study from Iran - Choshaly, Sahar Hosseinikhah (Turyzm/Tourism, 2025)
This study examines the predictors of tourist attitudes towards local food along with intentions to visit a destination. This study is of great interest to research tourism in Iran. Specifically, it is the first to examine the impact of belief and familiarity as psychological factors on tourist attitudes towards local food and intentions to visit a destination. The sample consisted of 200 Iranian tourists visiting the city of Lahijan. Data were analyzed using descriptive statistics and structural equation modelling and the findings recognized familiarity as the most influential factor affecting attitudes toward local food, followed by epistemic, emotional, health and prestige value as well as food neophobia. However, interaction value, price and taste are not associated with attitudes towards local food. The article offers practical marketing strategies for tourism marketeers regarding the important determinants of intentions to visit a destination. This research can help authorities in charge of business promotion as to what is more likely to attract tourists and their use of tourism resources.